Pengenalan Seni Suara Dharmagītā “Sekar Agung” Berbasis Multimedia Interaktif - Putu Eka Sura Adnyana; I Made Ade Prayoga (Sphatika: Jurnal Teologi, 2021)
The Interactive Multimedia-based Sekar Agung Art Sound Introduction is the newly cutting edge innovation in order to introduce Balinese culture especially Sekar Agung which is particularly a part of Dharmagita – Dharmagita is a sacred verse of Hindus. Furthermore, in this modern era, Balinese Hindus mostly unable to acknowledge the true meaning of that relic lullaby such as what is Sekar Agung, what is it containing, what else is including in Sekar Agung. The Interactive Multimedia-based Sekar Agung Introduction was incorporating the MDLC Multimedia Development Life Cycle method with Adobe Flash as it main software and ActionScript 3.0 as it programming operation. The final result of this research was a form of Interactive Multimedia application which contained information, course and material, audio and video related to Dharmagita, Sekar Agung and also a Quizzes to evaluate the user’s knowledge about Sekar Agung. This application could be utilized as Learning Reference and an Introduction of Sekar Agung which helps it become understandable, more innovative and interactive.